Assessment of the Potential Health Risks Associated with the Plumbum, Cadmium, Zinc and Nickel Content in Fish Tissue Collected from Retention Pond - Nabila Natasya Abdullah; Eh Rak, Aweng (Universitas Airlangga, 2025)
Introduction: The presence of heavy metals in fish constitutes a potential health risk to human consumers. This research aims to address this issue by determining the concentration of heavy metals in fish samples collected from retention ponds and assessing potential health risks for those who consume fish caught from the ponds. The primary objectives involve assessing the concentrations of heavy metals in fish tissues. Additionally, the study aim to evaluate potential health risks. Methods: The Atomic Absorption Spectrophotometer was employed to quantify heavy metal concentrations, while health risk assessments were based on EDI, THQ, HI, and CR calculations. Results and Discussion: The findings indicate a metal distribution pattern in the order of Zn> Pb> Ni> Cd and the observed value is lower than the maximum level permitted by FAO. The THQ and HI values for all studied metals were found to be below 1, signifying a lack of adverse non-carcinogenic health effects on consumers. At the same time, the cancer risk values for examined heavy metals are well below the value 10-4 which is consider as acceptable cancer risk, except Ni. CR value for Ni was recorded higher than 10-4 approaching higher limit of acceptable limit, suggesting a heightened cancer risk for consumers who consume these fish throughout their entire lifespan. Conclussion: The findings from this research have significant implications, contributing to various aspects of public health, environmental management, and regulatory measures.